The Ultimate Solution for the Growing threat of Crimean Congo Hemorrhagic Fever (CCHF) during Forthcoming Eid-ul-Adhas - Irfan, Seema (Infectious Diseases Journal of Pakistan, 2023)
The Crimean Congo Hemorrhagic Fever (CCHF) virus can cause severe disease in humans with case fatality rate being up to50%.1 The first case was reported from Pakistan in 1976 and has since remained endemic involving many regions of the country.2 The virus is primarily transmitted to people from Hyalomma tick bites following an incubation period of 1-3 days. Majority of cases occur biannually during the fall and spring seasons. They are linked to the life cycles of the ticks and human contact with asymptomatic viremic animals during slaughter and animal handling. Moreover, human-to-human transmission can occur resulting from close contact with the blood, secretions, organs and other bodily fluids from an infected person, incubation period of disease in that case is 5-6 days. CCHF is not a rare disease in Pakistan with 50-60 cases being reported annually.3 During last few years, it has been noticed that there has been an upsurge in the number of cases around Eid-ul-Adha. During this time in 2013 and 2014, a total of 58% and 62% of the CCHF cases were observed respectively.4 In 2016, up to the month of August, the Aga Khan Laboratory has reported 55 CCHF positive cases out of which 62% of these occurred between the month of June and August (unpublished data). One can speculate that this rise is may be due to unregulated animal transit across the country, compromised hygiene during animal slaughter, inadequate knowledge and awareness about the disease among animal handlers. In Pakistan, as per legislation, animals should be slaughtered at designated facilities with veterinary physician’s certification.5 Conversely, during Eid-ul-Adha, the sale of domestic animals is less regulated and the local authorities do not control health checks on the livestock and generally little is done to reduce tick infection among them. Moreover, there is anincrease in animal movement from endemic areas to major cities. It is common practice that people purchase these animals preceding Eid and keep them in individual houses from few days to weeks; leading to an increased exposure with the animals harboring the tick virus. In addition, non-professional butchers sacrifice animals in the house premises or on the road side without taking protective measures. It is imperative that government should play it’s role to contingency plan to stop the transmission of CCHF. Firstly, majority of animal slaughtering should be practiced in the designated slaughter houses using adequate personal protective equipment (PPE) including gloves, glasses and plastic gowns. Likewise, during Eid-ul-Adha, municipalities of the large cities should organize special temporary centers for slaughtering based on standard protocols. As a short term measure, public awareness messages regarding pertinent precautionary measures should be spread via media and social network coverage. Similarly, not only a health care plan should be prepared for handling outbreak situations but these measures should also be passed on to other public and private hospitals across the country. Therefore in order to prevent future consequences caused by ‘CCHF’, it is essential to not only acknowledge but to implement on such measures that have been mentioned above.